2010
DOI: 10.1007/s11524-009-9426-8
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Housing and Neighborhood Conditions and Inflammatory Markers among Middle-Aged African Americans

Abstract: Adverse housing and neighborhood conditions are independently associated with an increased risk of various diseases and conditions. One possible explanation relates to systemic inflammation, which is associated with these adverse health outcomes. The authors investigated the association between housing and neighborhood conditions with inflammatory markers using data about 352 persons aged 49-65 years from the African American Health study. Participants were identified by a multistage random selection process i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Only a few existing studies have examined relationships between inflammation and neighborhood factors (Petersen et al, 2008; Schootman et al, 2010), and only one of which we are aware has gone beyond conventional neighborhood socioeconomic (SES) characteristics to investigate other sociogeographic aspects of local environments that may be linked to high CRP (Nazmi et al, 2010). We report new evidence from 2007 Boston Metropolitan Immigrant Health & Legal Status (BM IHLSS) data that neighborhood level disorder and social capital are associated with high CRP among Brazilian migrant adults residing in the Boston Cambridge Quincy metropolitan statistical area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few existing studies have examined relationships between inflammation and neighborhood factors (Petersen et al, 2008; Schootman et al, 2010), and only one of which we are aware has gone beyond conventional neighborhood socioeconomic (SES) characteristics to investigate other sociogeographic aspects of local environments that may be linked to high CRP (Nazmi et al, 2010). We report new evidence from 2007 Boston Metropolitan Immigrant Health & Legal Status (BM IHLSS) data that neighborhood level disorder and social capital are associated with high CRP among Brazilian migrant adults residing in the Boston Cambridge Quincy metropolitan statistical area.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent research has identified psychosocial factors that may be associated with inflammatory processes, such as chronic and acute stressors, social support and poor psychological health (McDade et al, 2006; Ranjit et al, 2007; Uchino, 2006). Yet only a handful of studies have investigated relationships between neighborhood sociogeographic environments, in which stressors may be generated and social support forged, and inflammation (Liang et al, 2008; Nazmi et al, 2010; Petersen et al, 2008; Schootman et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Prior research suggests that associations of inflammation with individual and neighborhood SES vary across demographic groups, with several studies showing inconsistent associations in ethnic minorities (18, 3739). However, few studies have examined these associations in Latinos, who form a large and growing segment of the US population (40), and who are at disproportionate risk for certain CVD risk factors including obesity and type 2 diabetes (41, 42).…”
Section: Introductionmentioning
confidence: 99%
“…Older housing has also been associated with higher rates of infection in children [53], potentially leading to higher rates of inflammation. However, a study of middle-aged African Americans showed no difference in markers of inflammation by housing conditions [54], although they did not specifically consider age of housing. A higher proportion of older housing is also correlated with lower income and education levels and could be associated with other social variables that may explain our findings as well.…”
Section: Discussionmentioning
confidence: 99%